ECONOMIC ASSESSMENT OF GROWTH POTENTIAL OF EFFICIENCY IN AGRICULTURAL PRODUCTION - Yusipova, Alexandra; Silko, Elena; Khashir, Aslan; Kolonchin, Kirill (Revista Inclusiones, 2020)
The study’s main goal is to perform an objective economic assessment of the potential for the improved performance of agricultural production. Based on the study results, the authors carry out a comprehensive analysis and assessment of fixed asset investment in the agricultural sector, innovative activity in agrarian sub-industries, as well as shares of plant cultivation and animal husbandry in agricultural products. The authors have formulated and substantiated the following conclusions: one of the key potential areas for the improved performance of agriculture is the development of innovative technologies. In 2011-2018, the number of people employed, fixed asset costs and gross output of products in current and comparable prices increased at a high rate, showing the industry’s achievements and possibilities for further expansion of production.